Peran Praktikum dalam Kurikulum Merdeka untuk Meningkatkan Keterampilan Mendengar Siswa Madrasah Aliyah Putri Al- Ishlahuddiny - Hikmatus Suadah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
This research aims to describe the role of practicum in independent curriculum learning to improve students' listening skills. This research method uses a descriptive qualitative method. The subjects of this research are X th grade students at MA Putri Al-Ishlahuddiny. The research instrument uses documentary observation and interviews. The results of this research indicate that the implementation of practicum to improve the istima’ skills of class media